PROCEDURAL AND TACTICAL FEATURES OF THE EXAMINATION DURING THE PRE-TRIAL INVESTIGATION OF WAR CRIMES (Bulletin of criminological association of Ukraine, 2023)
In this article, it has been emphasized that during the investigation of war crimes, the role of the inspection of the scene of the incident is indisputably important, since during its conduct it is possible to record trace information that indicates the commission of war crimes, which consist in the violation of the customs and laws of war, and to document their consequences. It has been noted that the inspection of the scene of the incident is an urgent investigative (search) action, because it is carried out first of all from the moment of receiving information about the commission of a criminal offense and consists in the fastest possible investigation of the scene of the incident and the territory adjacent to it with the aim of identifying, fixing and extracting the maximum amount of evidence information in its original form. It has been indicated that the grounds and procedural procedure for conducting an inspection of the scene of the incident are defined in Art. Art. 104–106, 223, 233, 237, 238 and 615 of the Criminal Procedure Code of Ukraine. It has been found that the specifics of the tactics of inspection of the scene of the incident during the pre-trial investigation of war crimes are determined by the features determined by the criminal law and forensic characteristics of the specified crimes, which are directly reflected in the environment of the scene of the incident and the trace picture of the specified offenses. It has been emphasized that the effectiveness and efficiency of the inspection of the scene during the pre-trial investigation of war crimes lies in the correct organization of the activities of the participants of this investigative (search) action at all stages of its implementation - preparatory, working, final. The peculiarities of preparation, direct conduct and recording of the progress and results of the inspection of the scene of the incident during the pre-trial investigation of war crimes have been determined.
Keywords: war crimes; inspection of the scene; grounds; procedural order; tactical features; pre-trial investigation; collection of evidence